2013
DOI: 10.3892/ijmm.2013.1455
|View full text |Cite
|
Sign up to set email alerts
|

Rac regulates collagen-induced HSP27 phosphorylation via p44/p42 MAP kinase in human platelets

Abstract: Abstract. We previously reported that the collagen-induced phosphorylation of heat shock protein (HSP) 27 via p44/p42 mitogen-activated protein (MAP) kinase is sufficient to induce the secretion of platelet-derived growth factor (PDGF)-AB and the release of soluble CD40 ligand (sCD40L) from human platelets. It has been shown that Rac, which belongs to the Rho family of small GTPases, is involved in the collagen-induced platelet aggregation. In this study, we investigated the role of Rac in the collagen-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Regarding HSP27 in human platelets, we have reported that ADP-or collagen-induced HSP27 phosphorylation is mediated through p44/p42 mitogen-activated protein kinase (MAPK), and HSP27 phosphorylation is accompanied with both the secretion of PDGF-AB and the release of sCD40L [28,29]. In addition, we showed that Rac positively regulates collagen-induced HSP27 phosphorylation via p44/p42 MAPK [30]. Moreover, in our recent studies [31,32], we demonstrated that phosphorylated-HSP27 is released from platelets stimulated by collagen or TRAP in diabetic patients.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Regarding HSP27 in human platelets, we have reported that ADP-or collagen-induced HSP27 phosphorylation is mediated through p44/p42 mitogen-activated protein kinase (MAPK), and HSP27 phosphorylation is accompanied with both the secretion of PDGF-AB and the release of sCD40L [28,29]. In addition, we showed that Rac positively regulates collagen-induced HSP27 phosphorylation via p44/p42 MAPK [30]. Moreover, in our recent studies [31,32], we demonstrated that phosphorylated-HSP27 is released from platelets stimulated by collagen or TRAP in diabetic patients.…”
Section: Introductionmentioning
confidence: 85%
“…Regarding HSP27 phosphorylation in human platelets, we previously showed that Rac postitively regulates collagen-induced HSP27 phosphorylation at a point upstream of p44/ p42 MAPK [30]. In addition, we demonstrated that the TRAP-stimulated activation of Akt is involved in the phosphorylation of HSP27 and its subsequent release in diabetic patients [32].…”
Section: Effects Of Trap On the Phosphorylation Of P38 Mapk P44/p42 mentioning
confidence: 91%
See 1 more Smart Citation
“…In response to collagen, it has been reported that p38 MAP kinase is activated and regulates HSP27 phosphorylation in the process of human platelet activation [ 18 ]. We have recently reported that Rac, a low-molecular weight GTP-binding protein, regulates collagen-induced HSP27 phosphorylation via p44/p42 MAP kinase in human platelets, leading to the secretion of PDGF-AB [ 19 ]. However, the clinical relevance of HSP27 phosphorylation in human platelets has not yet been precisely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the members of MAP kinase superfamily such as p38 MAP kinase are involved in the phosphorylation of HSP27 in the process of human platelet activation (13,19). We previously reported that Rac, a low-molecular weight GTP-binding protein, regulates HSP27 phosphorylation stimulated by collagen via p44/p42 MAP kinase in human platelets (20). Furthermore, we have recently shown that phosphorylated-HSP27 stimulated by collagen or thrombin receptor-activating protein (TRAP) in the platelets of type 2 DM patients is released together with the secretion of PDGF-AB (21,22).…”
Section: Ristocetin Induces Phosphorylated-hsp27 (Hspb1)mentioning
confidence: 99%